Faktor Eksternal dan Internal Strategi Penginjilan Menghadapi Penganiayaan di Suku Terabaikan - Elizabeth Situmorang (Pengarah: Jurnal Teologi Kristen, 2021)
The evangelism strategy is a plan that must be done before the mission. Considering the various cases of persecution that befell several evangelists and the people of Indonesia. Especially in neglected tribal areas, such as Papua, cases of persecution are increasingly widespread. This has caused various physical and psychological injuries to some evangelistic groups and foundations. Some evangelists make a new breakthrough to improve the quality of evangelism in neglected areas. Several strategies have been devised in an attempt to reflect the personality of Christ. With the evangelism strategy from both internal and external factors, it is expected to be able to face the persecution that occurs in the mission. Therefore, evangelism strategies must be planned, understood and used as a precaution to deal with cases of persecution that occur.